Status of elbow myoelectric prosthesis: CINVESTAV-IPN prosthesis - Ramírez-García., A.; Toledo., C.; Leija., L.; Muñoz., R. (Revista Mexicana de Ingenieria Biomedica, 2009)
Advances of the prostheses had allowed people who lost an extremity to win back their normal life and live it with fewer limitations. Traditional commercial elbow prosthesis has at least two degrees of freedom: flexion-extension and humeral rotation; but the human arm has 22 degrees of freedom. Thus, it is important to realize that the prosthetics have a long way to go. Furthermore, the higher the amputation level, the greater the demand on the fitting technique. This work describes some elbow myoelectric prostheses of different characteristics, which have advantages and drawbacks. Also, a current status of CINVESTAV-IPN prosthesis is described. The prosthesis is formed with a parallel mechanism of actuators. That allows an increase in the number of active degrees of freedom and therefore the range of motion. This enhancement let it carry out natural movements, which is a challenge in the evolution of prosthetics devices. Finally, a comparison of CINVESTAV-IPN prosthesis with others is discussed.